Reflections of the Age of Enlightenment in Eighteenth-Century Travel Writing of Lithuanian Jesuits - Kvizikevičiūtė, Milda (Senoji Lietuvos literatūra, 2020)
The history of travel is becoming increasingly attractive to cultural historians. Although the number of studies is growing, insufficient attention has so far been paid to travel writings within particular social groups. The aim of the paper is to present insufficiently researched examples of eighteenth-century travel writings by Lithuanian Jesuits, in which they relate of their journeys in Western Europe, and to discuss them against the overall context of travel writing of the Grand Duchy of Lithuania in the Age of Enlightenment. With his aim in mind, in this paper the author compares travel journals of different epochs, social strata, and sexes, assuming that Jesuit travel diaries might reflect the influence of the Jesuitic social status and education on the objects visited and on the prevailing narratives of travel writing. The study is based on the descriptions of three journeys of eighteenth-century Jesuits: the travel journal of Adalbert Bohuszewicz, rector of the Jesuit College of Polotsk, about his journey to Rome and back, a description of European travel by the former Jesuit Franciszek Ksawery Bohusz, and a travel guide to Rome by the former Jesuit Kazimierz Kognowicki. These travel diaries by eighteenth-century Lithuanian Jesuits follow the common trends of travel writing of their time: they display the presence of critical thinking and evaluation as well as a changed relation between the author and the ostensible reader. Although the aims of the three texts differ, it is evident that the authors made efforts not only to preserve information but also to stir the interest of the future travellers. Since urban secular and sacral spaces are often separated in travel descriptions, the article accentuates the descriptions of these spaces and possible shifts in them. The author of the paper expands on the descriptions of the urban space as it is there that the changes of the epoch can best be felt. The descriptions of cities become somewhat more cautious and critical. The examined travel writings show that their authors were acquainted with the latest literature and were aware of travel trends, as demonstrated by their visits to newly-discovered archaeological sites in Rome and southern Italy. The impact of the epochs is best seen in the descriptions of sacral buildings. The travel journals of the eighteenth century no longer contain vivid stories of martyrdom, which flourished and were very descriptive in the travel diaries of the Baroque period. The investigation shows that compared to travel writings by the laity and the representatives of other monastic orders, the travel diaries of the Jesuits tend to focus on ‘Jesuit’ objects: descriptions of colleges and sacral buildings. More emphasis is given to the personalities of Ignatius of Loyola and Stanislaus Kostka. However, speaking in general, the examined sources more reflect the period’s established traditions of travel writing than manifestations of the collective identity of a social group.